2017
DOI: 10.1007/s13224-017-0985-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment at 11–14-Week Antenatal Visit: A Tertiary Referral Center Experience from South India

Abstract: Majority of fetal abnormalities can be detected, and majority adverse pregnancy outcomes can be predicted at 11-14-week antenatal visit, although this study shows high screen positivity and low specificity in a tertiary referral unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Model developers varied candidate predictors because of their availability in the setting of intended use 20,21 or to investigate the contribution of novel predictors to model performance. 22,23 Three groups developed models using data derived from low-resource settings, 20,21,24 and the remainder were developed in higher-resource settings. Most included all women presenting for routine pregnancy care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Model developers varied candidate predictors because of their availability in the setting of intended use 20,21 or to investigate the contribution of novel predictors to model performance. 22,23 Three groups developed models using data derived from low-resource settings, 20,21,24 and the remainder were developed in higher-resource settings. Most included all women presenting for routine pregnancy care.…”
Section: Resultsmentioning
confidence: 99%
“…In some studies the full set of candidate predictors was not clear. 24,32 The most frequently included predictor was ethnicity. Ethnicity was identified as a predictor of stillbirth in both univariable and multivariable analyses in every study that evaluated it, but it was highly variable in classification, even among datasets from the same country and city (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vellamkondu A et al, conducted a study on risk assessment at 11-14 weeks gestation and observed that 8.63% of patient had deranged blood sugar levels. 10 Present study has reported 20% of the participants with raised liver enzyme values (SGOT > 50, U/L SGPT > 50 U/L). Elbishry GM et al, conducted a study in which they reported that 22% of the patients with preeclampsia had deranged LFT.…”
Section: Sensitivity Specificitymentioning
confidence: 46%
“…9 Uterine artery doppler waveform analysis also has the best predictability at 22-26 weeks period of gestation. 10 Resistance to blood flow within uteroplacental circulation is transmitted upstream to the uterine arteries. 11 Faulty trophoblastic invasion of the spiral arteries results in diminished placental perfusion and upstream increased uterine artery resistance; resulting in increased uterine artery pulsatility index (PI) or resistance index (RI) and persistence of early diastolic notch.…”
Section: Introductionmentioning
confidence: 99%